2007
DOI: 10.1590/s0031-10492007002200001
|View full text |Cite
|
Sign up to set email alerts
|

Uso nocturno de perchas en dos especies de Anolis (Squamata: Polychrotidae) en un bosque Andino de Colombia

Abstract: In this study we recorded the use of sleeping site by Anolis "anoriensis" and Anolis mariarum in two study sites located in the montane forest of the extreme northern of Cordillera Central, Colombia. We also tested the occurrence of spatial segregation between the two species. Furthermore, we estimated perch availability in both study sites. Anolis mariarum slept more frequently on shrubs (51%) than other kinds of perches (ferns, herbs, trees), but did so in proportion to their availability. Anolis "anoriensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…The next group with high morphological diversity corresponds to montane forest assemblages and some studies of Colombian montane anoles indicate that at least three species are observed per locality (Hernández‐Ruz et al ., ; Caicedo et al ., ; Molina‐Zuluaga & Gutiérrez‐Cárdenas, ; Moreno‐Arias et al ., ). Cloud and Andean forests offer the same vegetal strata as lowland forests; species in these environments correspond to arboreal anoles and include morphotypes of canopy (MT4 and 10), understory anoles (MT3 and 6), and understorey and herbaceous anoles (MT1).…”
Section: Discussionmentioning
confidence: 99%
“…The next group with high morphological diversity corresponds to montane forest assemblages and some studies of Colombian montane anoles indicate that at least three species are observed per locality (Hernández‐Ruz et al ., ; Caicedo et al ., ; Molina‐Zuluaga & Gutiérrez‐Cárdenas, ; Moreno‐Arias et al ., ). Cloud and Andean forests offer the same vegetal strata as lowland forests; species in these environments correspond to arboreal anoles and include morphotypes of canopy (MT4 and 10), understory anoles (MT3 and 6), and understorey and herbaceous anoles (MT1).…”
Section: Discussionmentioning
confidence: 99%
“…Este patrón coincide con el estudio de García y colaboradores en el 2008 con Pristimantis jubatus, donde los individuos adultos ocuparon estratos más altos que los juveniles [36]. Pristimantis unistrigatus utilizó con mayor frecuencia las hierbas seguidas por arbustos, concordando con el estudio de Molina-Zuluaga y Gutiérrez-Cárdenas [37]. Esta preferencia se podría deber a la importancia de la estructura física de la percha para evitar la exposición frente a depredadores más que la preferencia del tipo de especie vegetal [38].…”
Section: N Percha Nocturnaunclassified
“…Diferentes hábitats proveen una gama diferente de recursos y condiciones para la existencia de un individuo (Nemes et al, 2006), su escogencia, implica un proceso de elección de los recursos espaciales que se encuentran a disposición en los distintos ambientes (Partridge, 1978;Molina-Zuluaga & Gutiérrez-Cárdenas, 2007), donde las especies prefieren espacios que les ofrezcan sitios para alimentación, reproducción, subsistencia y supervivencia (Vitt et al, 1997). El proceso de elección está determinado por la estructura física del ambiente, la fisiología del organismo, la disponibilidad de recursos, alimento, refugio o protección frente a depredadores y a las condiciones adversas del ambiente (Reaney & Whiting, 2003).…”
unclassified